Syndromic Craniosynostosis - Derderian, Christopher; Seaward, James (Seminars in Plastic Surgery, 2012)
Although most cases of craniosynostosis are nonsyndromic, craniosynostosis is known to occur in conjunction with other anomalies in well-defined patterns that make up clinically recognized syndromes. Patients with syndromic craniosynostoses are much more complicated to care for, requiring a multidisciplinary approach to address all of their needs effectively.This review describes the most common craniosynostosis syndromes, their characteristic features and syndrome-specific functional issues, and new modalities utilized in their management. General principles including skull development, the risk of developing increased intracranial pressure in craniosynostosis syndromes, and techniques to measure intracranial pressure are discussed. Evolving techniques of the established operative management of craniosynostosis are discussed together with more recent techniques including spring cranioplasty and posterior cranial vault distraction osteogenesis.
Keywords: syndromic craniosynostosis; intracranial pressure; posterior vault distraction; spring cranioplasty; midface distraction